Potential of Indole-3-Carbinol compounds from broccoli (Brassica oleracea var. italica) as natural aromatase blockers: In silico prediction and in vivo studies - Reski Amalia; Takashi Ohama; Ishwar Singh Parhar; Claude Mona Airin; Hiroshi Sato; Agung Budiyanto; Pudji Astuti (Open Veterinary Journal)
Background: Testosterone is a vital androgen hormone responsible for sex differentiation, producing male sex characteristics, spermatogenesis, and fertility. Abnormalities in testosterone levels, leading to reduced weight gain and reproductive capacity, pose a significant problem for livestock farmers. Although synthetic testosterone injection is a general strategy to restore hormone levels, it leads to a downregulation of testosterone production in livestock. Therefore, an alternative method that does not affect the safety of livestock products is needed. Studies showed that the abnormal conversion process from testosterone to estradiol (aromatization) causes high estradiol in male animals. Here, we analyzed the aromatase inhibitory activity of I3C extracted from the stem part of broccoli, which has beneficial effects on the reproductive system by unknown molecular mechanisms.